Odpowiedzi

2009-12-09T21:08:16+01:00
2009-12-09T21:17:18+01:00
3x - 3y + 4x = 8
3x - 15y = 5 - 9y

3x - 3y + 4x = 8 / :3
3x - 15y = 5 - 9y

x - y + 4/3x = 8/3
3x-15y = 5 - 9y

-y = -x - 4/3x + 8/3 /: (-1)
3x - 15y = 5 - 9y

y = x + 4/3x - 8/3
3x = 15y + 5 - 9y

y = x + 4/3x - 8/3
3x = 15 * ( x + 4/3x - 8/3 ) + 5 - 9 * ( x + 4/3x - 8/3 )

y = x + 4/3x - 8/3
3x = 15x + 20x - 40 + 5 - 9x - 12x + 24

y = x + 4/3x - 8/3
3x = 14x - 11

y = x + 4/3x - 8/3
3x - 14x = -11

y = x + 4/3x - 8/3
-11x = -11 /: (-11)

y = x + 4/3x - 8/3
x = 1

y = 1 + 4/3 - 8/3
x = 1

y = -1/3
x = 1

sprawdzenie

3x - 3y + 4x = 8 x = 1
3x - 15y = 5 - 9y y = -1/3

3 + 1 + 4 = 8
3 + 5 = 5 + 3